Integrasi Penilaian Tes dan Non-Tes dalam Pendidikan Agama Islam: Menuju Evaluasi Holistik untuk Pembelajaran Berkelanjutan - Mukmin, Mukmin; Nuraini, Nuraini (Yayasan Indonesia Emerging Literacy Education, 2024)
This study discusses the development and implementation of an assessment model for Islamic Education (PAI) that integrates both test and non-test techniques. The study is conducted through a comprehensive literature review encompassing various academic sources related to PAI assessment. The findings reveal that test techniques, such as multiple-choice questions and essays, are highly effective in assessing students' cognitive understanding of Islamic concepts. However, these techniques have limitations in evaluating the affective and psychomotor domains, which are also crucial in shaping students' character. On the other hand, non-test techniques, including observations, portfolios, and projects, are better suited for assessing affective and psychomotor aspects, providing a more holistic view of students' development. The combination of test and non-test techniques allows for a more comprehensive, fair, and holistic evaluation of all aspects of student learning, encompassing knowledge, attitudes, and skills. The implications of this study emphasize the importance of a holistic assessment approach in Islamic education, as well as the need for teacher training in the application of non-test techniques to ensure objectivity and validity in assessments. Thus, this research makes a significant contribution to improving the quality of Islamic education through assessments that are more adaptive, responsive, and relevant to students' needs in the modern era